Impact of Green Building Implementation on Health and Well-being of Building Users in Indonesia - Lendra, Lendra; Jesica, Jesica; Febrianty, Ruliana (Universitas Diponegoro, 2025)
This research conducts a systematic literature review, adopting the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, to examine the impact of green building implementation on health and well-being of users in Indonesia. The aim is to systematically categorize and analyze both the positive and negative effects of green building practices on occupants while identifying specific challenges that influence occupant comfort and safety. After analyzing articles from 2018 to 2023, a total of 15 papers were identified as primary resources for this study. The research found that green buildings have both positive and negative impacts. Positive impacts include minimal air pollution, good natural lighting, cool natural ventilation, and reduced noise disturbance. There are negative impacts such as insufficient natural lighting and ventilation in some areas, high noise levels, and security issues. This research provides insights for improving green building concepts to better support public health and occupational safety. By considering these impacts, future building environments can be designed to be healthier and more conducive to promoting public health and well-being. Future research should address operational challenges by exploring hybrid systems that integrate natural and artificial elements for consistent comfort, along with innovative solutions for noise and wildlife control.